Pengembangan Teori Dakwah Partisipatori Melalui Analisis Empirik Komentar Audiens pada Konten Youtube Ustad Khalid Basalamah - Prihatina, Nova; Putra, Bayu Darmawan; Khotimatunnisa, Ima; Sarbini, Ahmad; Iwan, Asep (CV. Rayyan Dwi Bharata, 2026)
The development of digital media has transformed da‘wah practices from one-way communication into dialogical and participatory spaces. YouTube, as an audio-visual platform, functions not only as a medium for disseminating religious messages but also as an interactive arena where meaning is socially constructed between preachers and audiences. This study aims to analyze the characteristics of audience comments, forms of participation in digital da‘wah, and their implications for the development of participatory da‘wah theory. Employing an interpretive qualitative approach with a multi-method digital textual analysis design, this research integrates qualitative content analysis, thematic analysis, digital ethnography, and social network analysis (SNA). The dataset consists of 2,907 audience comments collected from ten highly interactive YouTube videos by Ustadz Khalid Basalamah, selected through purposive sampling. The findings reveal four main categories of audience participation: spiritual appreciation and aspiration, fiqh-related inquiries, peer-to-peer dialogue and collaboration, and critical or alternative perspectives. Social network analysis indicates that audience interactions form clustered discursive communities with several central actors functioning as informal opinion leaders. These results demonstrate that digital da‘wah operates as a network-based participatory ecosystem, where audiences act as co-producers of religious meaning. This study contributes theoretically by reinforcing the Participatory Da‘wah Development Community (PDDC) model as a contemporary framework that emphasizes dialogical communication, distributed religious authority, and collective religious learning in the digital era.